2002
DOI: 10.1590/s0100-67622002000500010
|View full text |Cite
|
Sign up to set email alerts
|

Mobilização de reservas em sementes de Apuleia leiocarpa (Vogel) J.F. Macbr. (garapa) durante a embebição

Abstract: Quantificou-se a mobilização de reservas no eixo embrionário, nos cotilédones e no tegumento de sementes de Apuleia leiocarpa (garapa), durante a germinação. Os resultados mostram que houve aumento significativo das reservas de amido, ácido esteárico e proteína nos cotilédones durante o processo de embebição. Por outro lado, no embrião houve aumento significativo somente nos teores de manose, enquanto as reservas dos ácidos graxos mirístico, palmítico, esteárico, oléico e linoléico decresceram significativamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 9 publications
1
17
0
8
Order By: Relevance
“…Breakdown of seed oil reserves is known to occur after radicle emergence, being converted in starch or soluble sugars, which become the primary nutrient source during heterotrophic growth (NYKIFORUK and JOHNSON-FLANAGAN, 1999;PONTES et al, 2002;RODRIGUES et al, 2005). During rosewood seed germination, it was observed a decrease in the oil content of 40% between the first stage (0 cm) and the last stage of radicle emergence analyzed (5-7 cm) (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Breakdown of seed oil reserves is known to occur after radicle emergence, being converted in starch or soluble sugars, which become the primary nutrient source during heterotrophic growth (NYKIFORUK and JOHNSON-FLANAGAN, 1999;PONTES et al, 2002;RODRIGUES et al, 2005). During rosewood seed germination, it was observed a decrease in the oil content of 40% between the first stage (0 cm) and the last stage of radicle emergence analyzed (5-7 cm) (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Silva et al (1998) observed a protein level increase in the beginning of Dalbergia miscolobium seed imbibition. In Apuleia leiocarpa, protein contents increased with prolonged times of seed imbibition (PONTES et al, 2002). However, in seeds of Qualea grandiflora protein levels were constant during nine weeks of seed germination (PAULILO and FELIPPE, 1994).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations